Dellmann's textbook of veterinary histology - Eurell, Jo Ann; Frappier, Brian L. (Oxford : Blackwell, 2006)
Previous edition: published as Textbook of vet histology by H. Dieter Dellmann. 1998. CD-ROM in pocket.
Includes index.
Keywords: Veterinary histology; Histology; Anatomy, Veterinary